Forensic Photography: A Visual and Legal Record of Crime Scene: Fatima Fatima - Fatima, Fatima (International Journal for Electronic Crime Investigation, 2019)
Based on priority forensic photography is a source of documenting crime scenes. Currently it enables to signify a crime scene with every significant pieces of location and evidences. Adding to forensic investigation, crime scene photography provides a true and precise record of original scene and evidences relevant to surroundings. Crime scene photograph can illustrate a crime scene easily than verbal description by an investigator as it freezes time and records the evidences. It records all type of crime scenes such as fingerprints, impressions, injuries or bruises on skin in assault cases, human identification, bloodied body and knife in murder case etc. Scientific photography skills and techniques such as UV, IR and Fluorescence light filters are practiced to discover and preserve the hidden information during investigation. It is an integral part of criminal investigation by providing proper documented focused photographs to present actual story of the scene in the courtroom.